2019
DOI: 10.1136/bmjqs-2019-009524
|View full text |Cite
|
Sign up to set email alerts
|

Obstetric care navigation: results of a quality improvement project to provide accompaniment to women for facility-based maternity care in rural Guatemala

Abstract: Background Many maternal and perinatal deaths in low-resource settings are preventable. Inadequate access to timely, quality care in maternity facilities drives poor outcomes, especially where women deliver at home with traditional birth attendants (TBA). Yet few solutions exist to support TBA-initiated referrals or address reasons patients frequently refuse facility care, such as disrespectful and abusive treatment. We hypothesised that deploying accompaniers-obstetric care navigators (OCN)-trained to provide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(42 citation statements)
references
References 31 publications
2
19
0
Order By: Relevance
“…They indicated that dedicated units, taking into account the woman's global situation and with enough staff to call women who did not attend their appointments would be preferable. However, patient navigation during pregnancy has mostly been found effective in low and medium income countries (32). Additionally, our experience suggests that phone calls would not be enough because many women, particularly those whose prenatal follow-up care was inadequate, were really hard to reach for this study.…”
Section: A Perception That Depends On One's Experiencementioning
confidence: 90%
“…They indicated that dedicated units, taking into account the woman's global situation and with enough staff to call women who did not attend their appointments would be preferable. However, patient navigation during pregnancy has mostly been found effective in low and medium income countries (32). Additionally, our experience suggests that phone calls would not be enough because many women, particularly those whose prenatal follow-up care was inadequate, were really hard to reach for this study.…”
Section: A Perception That Depends On One's Experiencementioning
confidence: 90%
“…The study was a retrospective chart review of electronic data on obstetrical referrals collected as part of an obstetrical care navigation intervention, where primary clinical outcomes have already been reported [ 11 ]. Data were collected in collaboration with Maya Health Alliance, a primary care organization providing health services to rural communities in five Guatemalan provinces.…”
Section: Methodsmentioning
confidence: 99%
“…Reasons for this include the central cultural and spiritual role of traditional midwives in Maya healthcare, but also language barriers for speakers of Mayan languages accessing biomedical healthcare facilities and widespread experiences of discrimination and disrespectful or abusive biomedical care [ 7 8 ]. To address these barriers and improve facility birth rates for high-risk pregnancies, several interventions have been investigated, include the use of maternity homes, mobile health technology, care navigation, and rights-based auditing and accountability initiatives [ 9 10 11 12 13 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, indigenous women are at risk of poor maternal and perinatal health outcomes as they suffer greater social, economic, and emotional vulnerability with extreme levels of health inequalities [2,3,129,155]. Latin America (LATAM) is not an exception, extreme poverty, malnutrition, ethnic and linguistic differences, poor access to basic resources, education and health services [6,15,27,79,106] do not only expose indigenous women to discrimination but also put them at risk of serious pregnancy complications [6,9,17,29,109].…”
Section: Introductionmentioning
confidence: 99%